2018
DOI: 10.15171/ps.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymoquinone on Sperm Parameters, Apoptosis, Testosterone Level, and Oxidative Stress in a Mouse Model of D-Galactose-Induced Aging

Abstract: Background: The aging process is accompanied by low secretion of sex hormones and testicular apoptosis. The antioxidant properties of thymoquinone (TQ) may prevent the effects of aging. Therefore, in the present study, the effects of different doses of TQ were investigated on sperm parameters, testosterone level, apoptosis, and oxidative stress in a mouse model of D-galactose-induced aging. Methods: In this experimental study, 30 adult male mice were randomly divided into 5 groups. The control group did not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Human studies revealed that Nigella sativa seed extract is a practical approach to improve sperm motility [ 13 ]. Moreover, low doses of TQ (5–10 µg/mL) can increase sperm motility in culture media in normozoospermic men [ 45 ] and in aging mice [ 46 ]. In contrast, Iranpour et al [ 20 ] clarified that the high levels of TQ (20 µg/mL) could ultimately impair the sperm motility in culture media.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies revealed that Nigella sativa seed extract is a practical approach to improve sperm motility [ 13 ]. Moreover, low doses of TQ (5–10 µg/mL) can increase sperm motility in culture media in normozoospermic men [ 45 ] and in aging mice [ 46 ]. In contrast, Iranpour et al [ 20 ] clarified that the high levels of TQ (20 µg/mL) could ultimately impair the sperm motility in culture media.…”
Section: Discussionmentioning
confidence: 99%
“…After cooling, it was centrifuged at 1,000 x g for 10 min and then absorbed at 535 nm was read by a spectrophotometer and the malondialdehyde (MDA) concentration was calculated in nmol/g (Attari et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…After infiltrating with paraffin in 60º C , the molds were sectioned using rotary microtome. Hematoxylin-Eosin staining (Merck, Germany) was used for examining the samples and was investigated with optical microscopy [14].…”
Section: Histopathological Study Of Testicular Tissuementioning
confidence: 99%